Analisis pengaruh information asymetry terhadap earnings management dengan environment uncertainty sebagai variabel pemoderasi pada perusahaan manufaktur yang terdaftar di bursa efek Indonesia tahun 2018-2020 - Dewi, R. Rosiyana; Shierly (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of information asymmetry on earnings management with environment uncertainty as moderating variable in companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. This study uses secondary data, the data used in the form of financial statements of companies listed on the Indonesia Stock Exchange. The type of research used in this study is causal research, namely research that aims to find a causal relationship of the variables studied to answer research questions. The samples used in this study are manufacturing companies that are listed on the Indonesia Stock Exchange in the period of 2018-2020. Data were collected using purposive sampling. The total number of companies in the study sample is 152 companies with a study period of 3 years, resulting in 456 samples after outliers. This study uses a regression analysis moderation.The results of the study using linear regression analysis, descriptive statistic, and classic assumption test indicate that information asymmetry has a significant positive effect on earnings management. Then the results of linear regression analysis indicate that environment uncertainty does affect earning management. Furthermore, linear regression analysis revealed that environment uncertainty was able to moderate the relationship between information asymmetry and earnings management.